Um olhar sobre as dinâmicas e processos das disciplinas de metodologia e estágio na formação de professores a distância - Silva, Maiara Sobral (2015)
This work took as its starting point the need to investigate and reflect on the processes of teaching the disciplines of Education and Training Methodology in the Bachelor's Degree in Chemistry, in the form of distance learning. To this end, the following methodology was adopted: interviews with students from an undergraduate course distance of the State of Tocantins , as well as observation of actual classes of a degree course in the State of Rio Grande do Sul Through these observed If the processes and dynamics of teaching and learning in Distance Education. In addition, it sought to reverse the message flow, listening to the students involved in this process, their anxieties and expectations. Thus, with this study, I think another perspective of this form of education, leaving some focus on the material and history, to listen to those who are being trained in this form of teaching training of future teachers.